Acute pancreatitis-induced erythema multiforme. - Milano, A. (European Journal of Pediatric Dermatology, 2019)
In the literature we found cases of pancreatic involvement during Stevens-Johnson syndrome (2) and toxic epidermal necrolysis (1). On the other hand, we did not find any cases of erythema multiforme induced by viral acute pancreatitis. Erythema multiforme is a hypersensitivity dermatitis against different antigens and can be triggered by numerous infectious factors, including Herpes simplex, Mycoplasma pneumoniae, Staphylococcus aureus, Parvovirus B19, hepatitis A, B and C, ORF, yersiniosis, tularemia, Legionnaires’ disease, adenovirus, enterovirus, influenza, paravaccinia, smallpox, poliomyelitis and vaccinations. The clinical course of erythema multiforme is probably influenced by that one of the causal infection. Therefore, the characteristic recurrent course is probably related to the clinical course of Herpes simplex virus, which is its most frequent responsible cause.